ثورات الإباضية في طرابلس في العصرين الأموي والعباسي - د. عبدالباسط عبدربه محمد إدريس (Aljameai, 2026)
المستخلص : بعـد فـشل ثـورات الخوارج فـي المشرق الإسـلامي أواخر القرن الأول الهجـري انتقلوا إلى إفريقية وبـلاد المغـرب، وهناك انتهجوا نهجاً سرياً في الـدعوة والتنظـيم في الأمصار الإسلامية البعيدة، ووجد الخوارج في أرضهم الجديدة ميداناً خـصباً لنشر تعـاليمهم المعارضة للأنظمة الحاكمة في المشرق الإسلامي وكان من بينهم الخوارج الإباضية، الذين حظوا بتأييد واسع بين البربر، وعقب هذا التأييد بدأت المرحلة الثانية حيث انتقل الإباضيون من مرحلة الدعوة السرية إلى مرحلة التطبيق العملي لمبادئهم من خلال إطلاق عدة ثورات، مهد هذا الطريق لإقامة دولة قيض العباسيون أسسها في محاولتهم الأولى عندما أعلنوا قيامها في طرابلس حوالي عام 135 هـ / 753م، إلا أنهم نجحوا في إقامة دولتهم في المغرب الأوسط عام 160 هـ / 777م .Abstract:After the failure of the Kharijite revolts in the eastern Islamic world in the late first century AH, they migrated to Africa. There, they developed a clandestine approach to proselytizing and organizing in distant Islamic lands. The Kharijites found fertile ground in Africa to spread their teachings, which opposed the ruling regimes in the eastern Islamic world. Among them were the Ibadi Kharijites, who enjoyed widespread support among the Berbers. Following this support, the second phase began, in which the Ibadis moved from a stage of secret proselytizing to a stage of practical application of their principles through launching several revolts. This paved the way for the establishment of a state, the foundations of which the Abbasids laid in their first attempt when they declared its establishment in Tripoli around 135 AH , / 753 AD . However, they succeeded in establishing their state in the central Maghreb in 160 AH/  777AD.